Optimalisasi Aplikasi Financial Tracker berbasis Mobile dengan Penerapan Design Pattern MVVM untuk Mengelola Keuangan - Jaelani, Muhammad Naufal Hady Anshari; Asriningtias, Yuli (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
The use of an appropriate design pattern is crucial in application development to maintain code consistency and simplify task division. This research aims to optimize the development of a mobile-based financial tracker application by implementing the Model-View-ViewModel (MVVM) design pattern. MVVM was chosen because it separates business logic (Model), the interface (View), and presentation logic (ViewModel), making the code more structured, easier to test, and more maintainable. This study falls under the Research and Development (R&D) category, employing the waterfall model through the stages of analysis, design, implementation, testing, and maintenance. Data were collected through literature review and observation, and analyzed to evaluate the effectiveness of MVVM implementation. Our findings show that the mobile-based financial tracker application developed with MVVM design pattern successfully aids in financial management. Application testing results indicated significant performance improvements, with CPU efficiency at 74.8% on the RenderThread and 27.8% on the MainThread. This study contributes by demonstrating how MVVM improves responsiveness, simplifies real-time data synchronization, and enhances application flexibility and efficiency. These findings fill the gap in previous studies that have underexplored the technical aspects of financial application architecture.